Insights into the dynamics of mafic magmatic-hydromagmatic eruptions from volatile degassing behaviour: The Hverfjall Fires, Iceland - Liu, EJ; Cashman, KV; Rust, AC; Edmonds, M (Elsevier BV, 2018)
The style and intensity of hydromagmatic activity is governed by a complex interplay between the relative volumes of magma and water that interact, their relative viscosities, the depth of subsurface explosions, the substrate properties, and the vent geometry. Fundamental questions remain, however, regarding the role of magmatic vesiculation in determining the dynamics of magma-water interaction (MWI). Petrological reconstructions of magmatic degassing histories are commonly employed to interpret the pre- and syn-eruptive conditions during ‘dry’ magmatic eruptions, but the application of similar techniques to hydromagmatic activity has not yet been fully explored. In this study, we integrate glass volatile measurements (S, Cl, H2O and CO2) with field observations and microtextural measurements to examine the relationship between degassing and eruptive style during the Hverfjall Fires fissure eruption, Iceland. Here, coeval fissure vents produced both ‘dry’ magmatic (Jarðbaðshólar scoria cone complex) and variably wet hydromagmatic (Hverfjall tuff ring) activity, generating physically distinct pyroclastic deposits with contrasting volatile signatures. Matrix glass volatile concentrations in hydromagmatic ash (883 ± 172 [1σ] ppm S; 0.45 ± 0.03 [1σ] wt% H2O; ≤20 ppm CO2) are consistently elevated relative to magmatic ash and scoria lapilli (418 ± 93 [1σ] ppm S; 0.12 ± 0.48 [1σ] wt% H2O; CO2 below detection) and overlap with the range for co-erupted phenocryst-hosted melt inclusions (1522 ± 127 [1σ] ppm S; 165 ± 27 [1σ] ppm Cl). Measurements of hydromagmatic glasses indicate that the magma has degassed between 17 and 70% of its initial sulfur prior to premature quenching at variably elevated confining pressures. By comparing volatile saturation pressures for both magmatic and hydromagmatic glasses, and how these vary through the eruptive stratigraphy, we place constraints on the conditions of MWI. Crucially, our data demonstrate that the magma was already vesiculating when it encountered groundwater at depths of ...